A MODEL CASH WAQF LINKED SUKUK (CWLS): INSTRUMEN KETAHANAN PANGAN INDONESIA SDGs - Siregar, Kiki Hardiansyah; Manday, Chon Cho Reynols; Efendi, Bakhtiar (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Sustainability is a global concern that is embedded in every area of human life. This study aims to build an integrated model between Islamic social finance, government sukuk financing and Indonesia's food security SDGs. This paper is a type of library research with a qualitative approach. This study proposes an integrated model between Islamic social finance and government sukuk to build community food security through sukuk related to Salam cash waqf contracts. The model proposed in this study is the Cash Waqf Linked Sukuk (CWLS) under a Salam contract which can be used to provide food security solutions after the Covid-19 pandemic. The salam contract will help farmers and traditional market traders to produce food products on productive lands that have great opportunities to realize Indonesia's food security SDGs.